Predictors of optimal angiographic lesion outcomes in drug-coated balloon treatment for de novo coronary artery disease - Dong Oh Kang; Jong-Seok Lee; Bitna Kim; Yong-Hyun Kim; Sang-Yup Lim; Seong Hwan Kim; Jeong-Cheon Ahn; Ae-Young Her; Woo-Hyuk Song; Eun-Seok Shin; Sunwon Kim (Scientific Reports)
Abstract Drug-coated balloon (DCB) treatment is an emerging strategy for de novo coronary artery disease (CAD), but procedural optimization remains uncertain. This study analyzed 317 patients who underwent DCB-based intervention for de novo CAD and angiographic follow-up: SR (successful, stent-like result: diameter stenosis < 20% at follow-up angiography, n = 84, 93 lesions) and Non-SR (n = 224, 358 lesions) groups. Baseline clinical and lesion characteristics were similar, except that SR lesions had larger diameter. In SR lesions, specialty balloons were more frequently utilized (p = 0.025), and maximal balloon diameter and balloon-to-artery ratio were significantly greater compared to Non-SR lesions (p < 0.001 and p = 0.008). At a median 8-month follow-up, SR lesions exhibited larger minimal luminal diameter (MLD) and lower late lumen loss, with negative values indicating positive vessel remodeling. In multivariate analysis, post-DCB MLD (odds ratio 1.17 per 0.1 mm increase, p < 0.001) and balloon-to-artery ratio (odds ratio 1.43 per 0.1 increase, p = 0.002) were independent predictors for successful angiographic outcomes with thresholds of 1.95 mm for post-DCB MLD and 1.13 for balloon-to-artery ratio. In 47 patients, IVUS guidance resulted in balloon-to-artery ratio of 1.23 as calculated by QCA. The study demonstrated the importance of achieving maximal post-DCB MLD through aggressive lesion predilation, underscoring the need for refining procedural strategies. NCT04619277 (Impact of Drug-Coated Balloon Treatment in De Novo Coronary Lesion).